Indonesia’s maritime strategy facing The Kra Isthmus Canal agenda - Fika Monika; M. Baiquni; M. Pramono Hadi (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
This research will comprehensively analyze the Kra Isthmus Canal’s agenda and its possible impacts on Thailand and also to some other countries in ASEAN, specifically for Indonesia. By employing descriptive and qualitative methods, this study will investigate two types of paradigm through documentation and literature review from several studies in the past. The results are expected to encourage Indonesia to be more agile in adjusting steps to become the world's maritime fulcrum and also to sharpen the state sovereignty in sea policy